2023
DOI: 10.1097/crd.0000000000000529
|View full text |Cite
|
Sign up to set email alerts
|

Updates on the Global Prevalence and Etiology of Constrictive Pericarditis: A Systematic Review

Abstract: Constrictive pericarditis is a rare disease with poorly understood epidemiology. A systematic literature search was adopted to assess the region-and period-specific traits of constrictive pericarditis through Pubmed, EMBASE, and Scopus. Case reports and studies including less than 20 patients were excluded. The risk of bias was assessed through the Study Quality Assessment Tools developed by the National Heart Lung Blood Institute by 4 reviewers. Patient demographics, disease etiology, and mortality were the p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 32 publications
0
4
0
Order By: Relevance
“…For instance, the inci-dence of CP attributed to tuberculosis in India was 61% during the period of 1954-1985 and 93% during the period of 1985-2004, respectively [9]. A recent systematic review including 30 studies and over 11000 patients showed that tuberculosis remains the most frequent cause in Asia and Africa while previous cardiac surgery has become the predominant cause in North America and Europe [4]. Regardless, a part of CP patients remained idiopathic.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For instance, the inci-dence of CP attributed to tuberculosis in India was 61% during the period of 1954-1985 and 93% during the period of 1985-2004, respectively [9]. A recent systematic review including 30 studies and over 11000 patients showed that tuberculosis remains the most frequent cause in Asia and Africa while previous cardiac surgery has become the predominant cause in North America and Europe [4]. Regardless, a part of CP patients remained idiopathic.…”
Section: Discussionmentioning
confidence: 99%
“…There was a regional heterogeneity regarding etiologies worldwide. Tuberculosis was the predominant cause of CP in developing countries, while prior cardiac surgery was most frequent in North America and Europe [4]. Additionally, other potential causes encompassed asbestosis, trauma, malignancy, rheumatologic disease, and infection.…”
Section: Introductionmentioning
confidence: 99%
“…Constrictive pericarditis is an uncommon disease caused by several conditions, such as tuberculous pericarditis and nonspecific pericarditis. 1 Inflammation affects the visceral layer and parietal layer of the pericardium, leading to fibrosis, scarring, adhesion, thickening, calcification, and contracture of the pericardium, which restricts ventricular diastole and impairs ventricular function. 2,3 This also causes compression of the heart and the roots of large blood vessels, leading to restricted diastolic filling and resulting in several circulatory dysfunctions in the right atrium, including elevated vena cava pressure and reduced cardiac output.…”
Section: Introductionmentioning
confidence: 99%
“…Constrictive pericarditis is an uncommon disease caused by several conditions, such as tuberculous pericarditis and nonspecific pericarditis 1 . Inflammation affects the visceral layer and parietal layer of the pericardium, leading to fibrosis, scarring, adhesion, thickening, calcification, and contracture of the pericardium, which restricts ventricular diastole and impairs ventricular function 2,3 .…”
Section: Introductionmentioning
confidence: 99%